Real time 3-D ultrasound to MR cardiovascular image registration using a phase-based approach - Zhang, W; Noble, J; Brady, J; IEEE (2006)
We present a new method to globally affine register a real time 3-D ultrasound volume to a 2-D cardiovascular MR image. The local phase presentation of both images is utilized as an image descriptor of "featureness". Phase mutual information is employed as the similarity metric. The registration process is built in a multi-scale frame-work to estimate the global affine transformation using a differential technique. The accuracy of the final registration result is investigated and shown to give a RMS TRE error of 38.7mm and 20.3mm respectively for two volunteers, both of which are less than for an equivalent intensity-based method. © 2006 IEEE.